2016
DOI: 10.1136/jramc-2015-000563
|View full text |Cite
|
Sign up to set email alerts
|

Are Belgian military students in medical sciences better educated in disaster medicine than their civilian colleagues?

Abstract: IntroductionHistorically, medical students have been deployed to care for disaster victims but may not have been properly educated to do so. A previous evaluation of senior civilian medical students in Belgium revealed that they are woefully unprepared. Based on the nature of their military training, we hypothesised that military medical students were better educated and prepared than their civilian counterparts for disasters. We evaluated the impact of military training on disaster education in medical scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…Among the aspects covered were chemical, biological, radiological, disease pandemic, and nuclear training. Their study found that military students scored higher on knowledge and capability and were better prepared for disaster situations than their civilian counterparts, that is, medical science students [42]. Ingrassia and coworkers studied the disaster management educational and training initiatives at the postgraduate level in EU countries and found that face-to-face education was the most common teaching method used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the aspects covered were chemical, biological, radiological, disease pandemic, and nuclear training. Their study found that military students scored higher on knowledge and capability and were better prepared for disaster situations than their civilian counterparts, that is, medical science students [42]. Ingrassia and coworkers studied the disaster management educational and training initiatives at the postgraduate level in EU countries and found that face-to-face education was the most common teaching method used.…”
Section: Discussionmentioning
confidence: 99%
“…Although German students were highly motivated, the majority were not well educated regarding disaster medicine [22]. A study in Belgium indicated that the respondents wanted to increase their knowledge in this area and welcomed the introduction of specific courses into the standard medical curriculum [42].…”
Section: Discussionmentioning
confidence: 99%
“…These papers focus on the practical elements of disaster medicine, including the treatment of wounded, effect evaluation, first aid, and disaster medical education. [48][49][50][51][52] (2) "Hospital disasters." These papers also focus on practical elements of disaster medicine, including modular management, humanitarian relief, first aid management processes, and disaster emergency departments.…”
Section: Figurementioning
confidence: 99%
“…For a long time, disaster health was seen simply as an extension of conventional (non-disaster) emergency care and the literature [34,35] contains multiple complaints that the training of physicians does not prepare them for dealing with disasters and their aftermath. This situation is changing, encouraged by a better understanding of the unique, dynamic circumstances presented by disasters [18,21,36,37].…”
Section: Current Issues and Research In Disaster Health Community Resmentioning
confidence: 99%